Pengaruh Kemampuan Verbal dan Kemampuan Numerik Terhadap Kemampuan Menyelesaikan Soal Matematika - Fitriana Widya Lestari; Baidowi Baidowi; Wahidaturrahmi Wahidaturrahmi; Nyoman Sridana (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to determine the effect of verbal ability and numerical ability on the ability to solve math problems, to determine the effect of verbal ability on the ability to solve math problems, and to determine the effect of numerical abilities on the ability to solve math problems of class VIII students of SMP Negeri 3 Lingsar. This type of research is quantitative. The population of this study student of class VIII SMP Negeri 3 Lingsar. The sampling technique used cluster random sampling so that the sample was obtained by class VIII-A. The data analysis used was multiple linear regression analysis and simple linear regression analysis. From the results of the data analysis, there is a significant influence between verbal ability and numerical ability on the ability to solve math problems of class VIII students of SMP Negeri 3 Lingsar in the 2019/2020 school year and there is a significant influence between numerical abilities on students' ability to solve math problems. But there is no significant effect between verbal ability on the ability to solve math problems of class VIII students of SMP Negeri 3 Lingsar in the 2019/2020 school year.